THE NUREMBERG TRIAL IN THE DECADE: HISTORY, LEGAL CONSEQUENCES AND CURRENT CHALLENGES - ILIKA, MARYNA (Ehrlich's Journal, 2023)
The Nuremberg Trial of the Major War Criminals 1945–1946 was the International Military Tribunal in Nuremberg (Germany, November 20, 1945 – October 1, 1946) which considered the criminal actions of the leadership and individual organizations of the Third Reich in unleashing and conduct of the Second World War. The idea of creating an international tribunal originated in the USSR, it was stated in the governmental declaration “On the responsibility of Hitler’s invaders and their accomplices for the crimes they committed in the occupied countries of Europe” of October 14, 1942. After lengthy negotiations and meetings, the tribunal was formed from the representatives of four states: from the USSR – I. Nikitchenko (deputy chairman of the USSR Supreme Court), from the United States – F. Biddle (former US Attorney General), from Great Britain – D. Lawrence (chief judge of the United Kingdom Court of Appeals), from France – A. Donnedieu de Vabres (Professor of Law). The prosecution was formed on the same basis: from the USSR – the Attorney General of the USSR R. Rudenko, from the USA – the Attorney General of the USA R. Jackson, from Great Britain – the Minister of Justice of Great Britain H. Shawcross, from France – Professor of Law F. de Menthon. The defense was represented by 27 lawyers with 54 assistants. 403 public hearings were held, about 5.330 documents were considered (2.630 were provided by the prosecution, 2.700 by the defense) [10]. The defendants were charged with four counts: conspiracy to commit crimes against peace, unleashing the war of aggression, crimes against humanity, and war crimes. The trial lasted almost a year. The testimony of 280 witnesses was heard. Protocols and evidence amounted to 40 volumes. It was the Nuremberg Tribunal that had consequences for the formation of the international legal mechanism of criminal prosecution for the commission of crimes, the social danger of war crimes was first formed and defined, the composition of most war crimes was developed, and the determining features of criminally punishable behavior were established.